Global stabilization of linear time-varying delay systems with bounded controls - V. N. Phat (2018)
© 2015 Elsevier Ltd. All rights reserved. The objective of the present paper is to give an explicit solution to the global stabilization problem for linear time-varying delay systems with bounded control. Lyapunov function method with LMI techniques are proposed in order to derive novel sufficient conditions for designing stabilizing feedback control in terms of LMIs. The proposed result is illustrated through a numerical example.